Dinamika Pendidikan Islam Masa Daulah Abbasiyah dan Peranannya dalam Perkembangan Pendidikan - Jasmanidar, Ike Wahyuni; Zulmuqim; Fauza Masyhudi (Journal of International Multidisciplinary Research, 2023)
This abstract discusses Islamic education during the Abbasid Daulah era. Education is a place where someone interacts or the teaching and learning process takes place with the learning environment. Islamic educational institutions are places where someone strives to increase students' faith, understanding, appreciation and practice of the Islamic religion so that they become individuals who believe and are devout in personal life, religion, society, nation and state. Islamic education began to develop from the time of the Prophet, the time of Khulafaur Rasyidin, the time of the Umayyah Daulah, the time of the Abbasid Daulah, until the present. Islamic education during the time of the Abbasid Daula experienced a golden age, at which time Islamic education was marked by amazing progress in the fields of science, culture and civilization, so that its existence can be proven through various sources of information recorded in history books and observers of history from various parts of the world that were once ruled by Islam. The aim of writing this article is to discuss the dynamics of Islamic education during the Abbasid period and its role in the development of Islamic education. The research method used in this research is library research. Sources of information for this research were obtained through various sources, print media, online media regarding the topics discussed. The results of the research in this article can be seen from the development of Islamic educational institutions that developed during the Abbasid period, including: mosques, Al-Hawanit al-Wariqien (bookstores), al-manazil al-ulama (houses of ulama), literary studios , madrasas, libraries and observatories, kuttabs, lower education in palaces, hospitals and badiahs.